Peran Badan Penangulangan Bencana Daerah (BPBD) dalam Menanggulangi Bencana Erupsi Gunung Lewotobi Laki-Laki di Kecamatan Wulanggitang dan Kecamatan ILE BURA Kabupaten Flores Timur - Yovita Serviana Ona Watu; Theny I. B. K. Pah; Belandina L. Long; Cataryn V. Adam (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the role of the Regional Disaster Management Agency (BPBD) of East Flores Regency in managing the eruption disaster of Mount Lewotobi Laki-Laki during the pre-disaster, emergency response, and post-disaster phases. The study employed a descriptive qualitative method involving 18 informants from BPBD and affected communities in Wulanggitang and Ile Bura Sub-districts. Data were collected through observation, interviews, and documentation. The findings show that during the pre-disaster phase, BPBD implemented preparedness measures through disaster-prone area mapping, the establishment of Disaster Preparedness Teams and Disaster-Resilient Villages, public outreach, and the use of local wisdom. However, outdated contingency plans, limited early warning systems, weak relocation efforts, and low public awareness contributed to panic and casualties during the eruption. In the emergency response phase, BPBD successfully coordinated evacuation efforts, established emergency posts, and distributed logistics effectively. Nevertheless, displaced communities experienced discomfort due to prolonged emergency conditions and limited fulfillment of basic needs in temporary shelters. In the post-disaster phase, BPBD conducted rehabilitation and reconstruction through transportation recovery, trauma healing programs, and permanent housing development based on the Rehabilitation and Reconstruction Plan (R3P). However, limited funding and delays in reconstruction processes remained major challenges. Therefore, improving coordination, institutional capacity, disaster communication, and community participation is essential for effective disaster management.